Pengaruh Kualitas Produk, Harga dan Viral Marketing Terhadap Keputusan Pembelian Mie Gacoan Cabang Dinoyo (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Angkatan 2020 Universitas Islam Malang) - Sahidah, Putri Nuramrina; Rachma, N.; Arsyianto, Muhammad Tody (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this study is to ascertain how Mie Gacoan, Dinoyo Branch, Purchase Decision (Y) is influenced by Product Quality (X1), Price (X2), and Viral Marketing (X3). This study employs quantitative methods. by gathering the opinions of one hundred students from the Islamic University of Malang's 2020 class in the Faculty of Economics. The questionnaire distribution technique was employed to gather data, and samples were gathered using the formula approach created by Malhotra (2006). SPSS was utilized in this study's data analysis. A variety of testing methods are employed, such as multiple regression, instrument testing, normality testing, classical assumption testing, hypothesis testing, and coefficient of determination testing. Product Quality (X1), Price (X2), and Marketing Viral (X3) have a simultaneous relationship, according to the test findings. Keywords: Product Quality, Price, Viral Marketing, Purchase Decisions.